Translation Strategy for Idioms in “The Schools For Good and Evil” - Ridwan, Nurhidayah; Putri, Astari Amalia (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2025)
This study aims to analyze and explain the translation strategy of the idioms used in the film